Filariasis of parti-colored bats: phylogenetic analysis, infection prevalence, and possible vector mite identification - Bednarikova, Sarka; Danek, Ondrej; Dundarova, Heliana; Nemcova, Monika; Piacek, Vladimir; Zukalova, Katerina; Zukal, Jan; Pikula, Jiri (Frontiers in Veterinary Science, 2025)
IntroductionThe epidemiology of filarial infections is a neglected area of bat research, with little information on filarial species diversity, life cycles, host ranges, infection prevalence and intensity, parasite pathogenicity, or competent vectors. Furthermore, molecular data for filarial worms are largely lacking.MethodsHere, we examined 27 cadavers of parti-colored bat (Vespertilio murinus) from Czech rescue centers for filarial infection using gross necropsy. We also used nested polymerase chain reactions targeting partial mitochondrial cytochrome c oxidase subunit I (COI) partial gene to detect and genotype filarial parasites within organs, and ectoparasites of V. murinus from Russian and Slovak summer bat colonies. Samples with mixed filarial infections were cloned to extract separate sequences. The COI gene sequences were then subjected to phylogenetic analysis and a phylogenetic tree constructed. Adult filarial worms were also screened for the bacterial symbiont Wolbachia, using a standard PCR targeting the partial 16S rRNA gene.ResultsTwo filarial nematode species were identified in single and mixed V. murinus infections, Litomosa sp. and a species of Onchocercidae. Adult Litomosa sp. nematodes were only recorded during necropsy of the abdominal, thoracic, and gravid uterine cavities of four bats. Molecular screening of organs for filarial DNA revealed prevalences of 81.5, 51.9 and 48.1% in Litomosa sp., Onchocercid sp. and co-infected bats, respectively. Adult Litomosa sp. worms proved negative for Wolbachia. The macronyssid mite Steatonyssus spinosus, collected in western Siberia (Russia), tested positive for Onchocercid sp. and mixed microfilarial infection.DiscussionOur results revealed high prevalence, extensive geographic distribution and a potential vector of filarial infection in V. murinus. Our data represent an important contribution to the field of bat parasitology and indicate the need for a taxonomic revision of bat-infecting filarial nematodes based on both morphological and molecular methods.